B-chromosome frequency stability in Prochilodus lineatus (Characiformes, Prochilodontidae) - Voltolin, Tatiana Aparecida [UNESP]; Senhorini, Jose Augusto [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP]; Bortolozzi, Jehud; Porto-Foresti, Fábio [UNESP] (Springer, 2010)
The genus Prochilodus includes individuals ranging in size from medium to large, being highly relevant for commercial and subsistence fishing. Prochilodus species have a diploid number of 2n = 54 chromosomes and up to seven supernumerary (B) microchromosomes. Previous research has shown that B frequency increased drastically in the Mogi-Gua double dagger u river population of Prochilodus lineatus in the early 1980s, whereas it remained about constant in the 1990s. Here we analyses B frequency in this population during the 2003-2007 period and have found that frequency has not changed significantly since 1987, and that these B chromosomes do not show the intra-individual variation in number that characterized them in the 1980s. This indicates that these B chromosomes have been neutralized, after their invasion, through their mitotic stabilization.
Keywords: Mitotic stability; Supernumerary chromosomes; Accumulation; Neutralization